Social media impact on societal security - Alnaqbi, Huda Hassan; Ali, Eman Ahmed Mohamed (Frontiers in Sociology, 2025)
This study explores the impact of social media on societal security by surveying 191 employees from various demographic backgrounds. Utilizing a structured questionnaire, the research highlights significant social, ethical, and security consequences, with 81.80% of participants reporting social impacts, 84.40% identifying ethical and behavioral effects, and 82.80% noting substantial security concerns. Despite the broad effects, no significant differences were observed based on gender, education, or social media platform usage. However, age-related variations emerged, with younger groups (23–30 and 31–40) reporting more profound effects compared to those aged 41–50. Based on these findings, the study recommends awareness campaigns addressing the risks of social media, the establishment of legal frameworks to enhance societal security, and the creation of a technical and legal support unit for victims of online incidents. The research calls for further qualitative investigations into hacking and damage cases to deepen understanding and guide effective policy measures.